Factors influencing investment decision making in the capital market (Case study at PT. Phillip Sekuritas Indonesia, Ambon branch) - Restia Christianty; Oki Nurul Asma Tualeka (Enrichment : Journal of Management, 2022)
This study aims to thoroughly examine the factors that influence investment decisions in the capital market, especially investors who invest in PT. Phillip Sekuritas Indonesia Ambon Branch. Data was collected using a google form-based questionnaire instrument involving 60 investor respondents who actively invest in PT. Phillip Sekuritas Indonesia Ambon Branch. Data is processed and analyzed using the SmartPLS 3.0 software application. The results of this study indicate that (1) the risk perception variable directly has a significant effect on investment decisions in the capital market; (2) the self-efficacy variable has a significant effect on investors' investment decision variables in the capital market. The existence of this research will have implications for the level of knowledge and awareness of the level of investment risk and self-efficacy owned by an investor, so that decisions can be made more effectively, considering that some investment products are high risk. This research offers an empirical model that explains the factors that influence investment decisions in the capital market by using a research model that combines psychological and demographic factors in making investment decisions in the capital market, so this research is important to do in order to add contribution and dedication to the literature review.